Managing geopolitical risks in global supply chains : Case study in the maritime and energy industry - Leskinen, Sanni (My University, 2026)
The frequency and significance of geopolitical risks and disruptions have increased drastically in the last decades, with the pandemic and ongoing conflicts in international relations. These risks have extensive disruptive impacts for global supply chains. The globalization, complexity and interconnectedness of global supply chains make them increasingly vulnerable to these disruptions. Therefore, it is crucial to research the ways in which geopolitical risks can be managed in global supply chains. This study investigates how geopolitical risks impact supply chains in the maritime and energy industry, and how they could be managed to avoid disruptions. It explores the factors that create vulnerability to these risks, and how the impacts vary between different kinds of supply chains. Furthermore, it analyses the differences in how local and global geopolitical risks cause impacts in these supply chains. The theoretical framework consists of literature on geopolitical risks, their impacts on supply chains and on supply chain risk management. Traditional supply chain risk management processes and strategies are presented, after which their applicability to geopolitical risks is discussed. This study is conducted as a single case study in a multinational corporation operating in the maritime and energy industry. It utilizes a mixed methods approach involving qualitative semi-structured interviews in the case company supply management organization, as well as quantitative secondary data from the case organization and the GPR index used to assess the level of geopolitical risk on a global and country-specific level. The results of the study suggest that the impacts of geopolitical risks are ultimately realized as price increases and delays and disruptions in deliveries. It finds that the impacts of geopolitical risks vary based on the type of supply category. Furthermore, it finds that some supply categories are more vulnerable to local geopolitical risks, while some to global geopolitical risks. It argues that traditional supply chain risk management strategies, such as diversification, are applicable to geopolitical risks, but the main challenge of managing them is the identification of the risks. In addition, it considers the challenges and contradictions related to implementing said risk management strategies.

Geopoliittisten riskien toistuvuus ja määrä ovat nousseet merkittävästi viime vuosikymmenien aikana, esimerkiksi pandemian ja jatkuvien kansainvälisten suhteiden konfliktien johdosta. Näillä riskeillä on merkittäviä haitallisia vaikutuksia globaaleihin toimitusketjuihin. Globaalien toimitusketjujen globalisaatio, kompleksisuus ja verkottuneisuus nostaa niiden haavoittuvuutta näille häiriöille. Siksi on tärkeää tutkia tapoja, joilla geopoliittisia riskejä voidaan hallita globaaleissa toimitusketjuissa. Tässä tutkimuksessa tarkastellaan sitä, miten geopoliittiset riskit vaikuttavat toimitusketjuihin merenkulun- ja energiateollisuuden toimialoilla sekä sitä, miten niitä voidaan hallita häiriöiden välttämiseksi. Tutkielma tarkastelee tekijöitä, jotka aiheuttavat alttiutta geopoliittisille riskeille ja sitä, kuinka vaikutukset vaihtelevat eri toimitusketjujen välillä. Lisäksi se tutkii sitä, miten lokaalit ja globaalit geopoliittiset riskit vaikuttavat toimitusketjuihin eri tavoin. Teoreettinen viitekehys muodostuu geopoliittisia riskejä, niiden vaikutuksia toimitusketjuihin, sekä toimitusketjun riskinhallintaa käsittelevästä kirjallisuudesta. Toimitusketjun riskinhallintaa lähestytään perinteisten riskinhallinta prosessien ja strategioiden kautta, minkä jälkeen niiden soveltuvuutta geopoliittisille riskeille analysoidaan. Tämä tutkimus on toteutettu tapaustutkimuksena, joka keskittyy yhteen globaalisti toimivaan yritykseen merenkulku- ja energiateollisuuden toimialalla. Se hyödyntää monimenetelmällistä lähestymistapaa sisältäen laadullisia puolistrukturoituja haastatteluita tapausyrityksen hankintaorganisaatiossa, sekä kvantitatiivista sekundääristä aineistoa tapausyrityksestä sekä GPR indeksistä, joka arvioi geopoliittisen riskin tasoa globaalisti sekä maakohtaisella tasolla. Tutkimuksen tulokset osoittavat, että geopoliittiset riskit johtavat hinnan nousuihin, sekä viiveisiin ja häiriöihin toimituksissa. Se osoittaa, että geopoliittisten riskien vaikutukset vaihtelevat riippuen hankintakategoriasta. Lisäksi se osoittaa, että jotkin hankintakategoriat ovat alttiimpia paikallisille geopoliittisille häiriöille, kun taas toiset globaaleille. Se väittää, että perinteiset toimitusketjun riskinhallintakeinot, kuten hajauttaminen, soveltuvat geopoliittisten riskien hallintaan, mutta suurin haaste niiden hallinnassa on riskien tunnistaminen. Tutkimus käsittelee myös haasteita ja ristiriitoja mainittujen riskinhallintakeinojen implementoinnissa.
Keywords: geopolitics; geopolitical risks; global supply chain; supply chain disruptions; risk management; supply management; maritime and energy industry; mixed methods; geopolitiikka; geopoliittiset riskit; globaalit toimitusketjut; toimitusketjuhäiriöt; riskinhallinta; hankinnan johtaminen; merenkulku- ja energiateollisuus; monimenetelmätutkimus